Continued maturation of auditory brainstem function during adolescence: A longitudinal approach. Issue 12 (December 2015) - Krizman, Jennifer; Tierney, Adam; Fitzroy, Ahren B.; Skoe, Erika; Amar, Jordan; Kraus, Nina
Highlights: We longitudinally tracked subcortical speech encoding in adolescents from ages 14–17. Spectral representation, response consistency, and envelope tracking decreased. Peak latencies were stable. Subcortical auditory development continues through adolescence. Abstract: Objective: Considerable attention has been devoted to understanding development of the auditory system during the first few years of life, yet comparatively little is known about maturation during adolescence. Moreover, the few studies investigating auditory system maturation in late childhood have employed a cross-sectional approach. Methods: To better understand auditory development in adolescence, we used a longitudinal design to measure the subcortical encoding of speech syllables in 74 adolescents at four time points from ages 14 through 17. Results: We find a developmental decrease in the spectral representation of the evoking syllable, trial-by-trial response consistency, and tracking of the amplitude envelope, while timing of the evoked response appears to be stable over this age range. Conclusions: Subcortical auditory development is a protracted process that continues throughout the first two decades of life. Specifically, our data suggest that adolescence represents a transitional point between the enhanced response during childhood and the mature, though smaller, response of adults. Significance: That the auditory brainstem has not fully matured by the end of adolescence suggests that auditory enrichment begun later in childhood could lead to enhancements in auditory processing and alter developmental profiles.